Phase and group velocity: a research-based educational activity driven by students on the topic on waves. Issue 1 (May 2021) - Buongiorno, Daniele; Michelini, Marisa; Faletič, Sergej
Abstract: To create an opportunity for students to re-elaborate their knowledge and offering them a working experience, 145 16-17 years old students from 6 classes from a Scientific Lyceum were involved in a research activity with responsibility in specific tasks involving conceptual learning of pulses and mechanical waves. Experiments by means of classical apparatus and mobile APPs were planned and performed by students themselves aiming at individuating the best way to prepare educational materials for peers. In this framework three different educational proposals were proposed to three different groups of students allowing them to point out weaknesses and strengths of the various approaches. The educational path aimed at clarifying the difference between phase and group velocity.